DISTRIBUSI HASIL TANGKAPAN GURITA (Octopus) DI DESA KALUPAPI KECAMATAN BANGKURUNG KABUPATEN BANGGAI LAUT: Distribution Of Octopus (Octopus) Catch In Kalupapi Village, Bangkurung District, Banggai Laut Regency - Nurfadila Matta; Aziz Salam; Nuralim Pasising (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2026)
This research aims to understand the distribution channels of octopus catches, catch results, fishermen's profits, and marketing margins of octopus (Octopus spp.) in Kalupapi Village, Bangkurung District, Banggai Laut Regency. Sampling was conducted from June to July 2024. This study uses a descriptive analysis of octopus catch distribution patterns. Primary data was obtained through interviews with respondents Meanwhile, secondary data consisted of document data gathered from the research location. The research results indicate that the distribution of octopus catches in Kalupapi Village, Bangkurung District, Banggai Laut Regency, is carried out through a trade channel, specifically from fishermen to collectors, from collectors to wholesalers, from wholesalers to agents, and finally from agents to the food processing industry. The average monthly income for octopus fishermen in Kalupapi Village, Bangkurung District, Banggai Laut Regency, is Rp 2,325,205. The average monthly profit for octopus fishermen in Kalupapi Village is Rp 1,587,534, and the octopus marketing margin is Rp 10,000/kg. Factors that affect the distribution and marketing of octopus catches include the volume of catches, selling prices, product quality, transportation, market demand, and the relationship between fishermen and traders.